A unique mathematical programming algorithm for performance optimization of organizational indicators in manufacturing sector. (3rd October 2019) - Merati, M.; Salehi, V.; Rafiei, A.
ABSTRACT: This study presents an integrated algorithm for the evaluation and optimization of manufacturing systems by considering managerial and organizational performance indicators. The proposed algorithm is composed of data envelopment analysis (DEA), fuzzy DEA and statistical methods. In order to achieve the goals of this study, a set of 12 criteria were chosen to indicate the application of the integrated method. The results showed DEA results have lower mean absolute percentage error (MAPE) than that of the fuzzy DEA. This study also analyzes and weights the indicators, and the results showed "research and development investment to production value" and "education and training investment per employee" indicators are the most effective indicators. This is the first study that introduces a unique algorithm for managerial and organizational factors. Second, it can handle data uncertainty due to existence of fuzzy mathematical programming in the algorithm. Third, weights of indicators are identified through robust statistical algorithm.